The role of statisticians in the response to COVID-19 in Israel: a holistic point of view - Itai Dattner; Reuven Gal; Yair Goldberg; Inbal Goldshtein; Amit Huppert; Ron S. Kenett; Orly Manor; Danny Pfeffermann; Edna Schechtman; Clelia di Serio; David M. Steinberg (BMC, 2022)
Abstract The COVID-19 pandemic cast a dramatic spotlight on the use of data as a fundamental component of good decision-making. Evaluating and comparing alternative policies required information on concurrent infection rates and insightful analysis to project them into the future. Statisticians in Israel were involved in these processes early in the pandemic in some silos as an ad-hoc unorganized effort. Informal discussions within the statistical community culminated in a roundtable, organized by three past presidents of the Israel Statistical Association, and hosted by the Samuel Neaman Institute in April 2021. The meeting was designed to provide a forum for exchange of views on the profession's role during the COVID-19 pandemic, and more generally, on its influence in promoting evidence-based public policy. This paper builds on the insights and discussions that emerged during the roundtable meeting and presents a general framework, with recommendations, for involving statisticians and statistics in decision-making.